2009
DOI: 10.1083/jcb.200906161
|View full text |Cite
|
Sign up to set email alerts
|

A dual function for Pex3p in peroxisome formation and inheritance

Abstract: Pex3p interacts with peroxisome retention factor Inp1p at the peroxisomal membrane and functions in the organelle’s segregation in addition to its biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 35 publications
1
64
0
1
Order By: Relevance
“…Basically, de novo formation of peroxisomes from the endoplasmic reticulum seems to be associated with the Pex3 protein, which plays also a role in peroxisome inheritance [86]. This peroxin is suggested to be essential for the formation of initial vesicular compartments termed pre-peroxisomes, which grow by recruiting newly synthesized peroxisomal membrane proteins and matrix proteins to form a mature peroxisome that multiplies by Wssion.…”
Section: Peroxisome Biogenesis and Abundancementioning
confidence: 99%
“…Basically, de novo formation of peroxisomes from the endoplasmic reticulum seems to be associated with the Pex3 protein, which plays also a role in peroxisome inheritance [86]. This peroxin is suggested to be essential for the formation of initial vesicular compartments termed pre-peroxisomes, which grow by recruiting newly synthesized peroxisomal membrane proteins and matrix proteins to form a mature peroxisome that multiplies by Wssion.…”
Section: Peroxisome Biogenesis and Abundancementioning
confidence: 99%
“…Pex3 regulates peroxisome biogenesis by acting as a docking factor for Pex19, the protein that recognizes the membrane PTS on PMPs and facilitates their post-transla-tional insertion into the peroxisomal membrane (20 -23); as a tether for the peroxisome inheritance factor Inp1 (24,25); as the receptor for Myo2 for peroxisome segregation in Yarrowia lipolytica (26); and as an anchor at the peroxisomal membrane for P. pastoris Atg30 and S. cerevisiae Atg36 (10,16). Additionally, Pex3 has been implicated in pexophagy in other species, such as the methylotrophic yeast Hansenula polymorpha, in which removal of ubiquitinated Pex3 from the peroxisomal membrane induces pexophagy, and in mammals, in which Pex3 overexpression induces pexophagy through a ubiquitin-dependent mechanism (27,28).…”
mentioning
confidence: 99%
“…Thus, Inp1p was concluded to be required for attaching peroxisomes to a then uncharacterized cortical anchor (Fagarasanu et al, 2005). The identification of mutants of Pex3p that are unable to recruit Inp1p to the peroxisomal membrane and exhibit the same phenotype as that of inp1D cells (Munck et al, 2009) indicated that there is a direct interaction between Pex3p and Inp1p. Pex3p is essential for peroxisome biogenesis and is integral to both the ER and the peroxisomal membranes (Hoepfner et al, 2005;Thoms et al, 2012).…”
Section: Commentarymentioning
confidence: 99%